PENGARUH POTENSI PETERNAK DALAM PENGEMBANGAN SAPI POTONG DI KECAMATAN DAMSOL KABUPATEN DONGGALA - Karunia Setyowati Suroto; Nurhasan . (Universitas Tribhuwana Tunggadewi, 2014)
Livestock business by farmers in the Damsol District of Donggala Regency is still traditionally held as a sideline business and low productivity. The objective of this study was to analyze the potential influence of basic and technology potencies farmers on the development of livestock in the Damsol District of Donggala Regency. The study was conducted from November 2011 to January 2012. Total respondents is 40 farmers selected from 123 farmers. Analyzed data included analysis of the basic potential of farmers, technology potential of farmers, and multiple linear regression analysis to determine the effects of the basic and technology potentials of farmers on the development of livestock business. The results showed that the ability of individual farmers in the district was good enough. Basic and technology potentials of the farmers were in medium category. Basic potential of farmer (experience, formal and non formal education, and communication intensity) and technology potential of farmer (feed technology, prevention and control of disease, and the selection of parent), simultaneously affected the development of livestock business at the Damsol District of Donggala Regency. Experience (basic potency), ability to provide feed (technology potency) and ability to select parent (technology potency) significantly influenced the development of livestock business